Reasonable Disagreement about Identifed vs. Statistical Victims - Daniels, Norman (The Hastings Center report, 2012)
People tend to contribute more—and think they have stronger obligations to contribute more—to rescuing an identified victim rather than a statistical one. Indeed, they are often disposed to contribute more to rescuing a single identified victim than a greater number of statistical ones. By an “identified victim,” I mean Terry Q., lying injured in the passenger seat of the wrecked automobile on the corner of Main Street and Broadway, or Jessica McClure, the child who fell into the Texas well in 1987 and whose family was sent USD700,000 in donations for her. We need not know their names, however, and we can accept a very minimal form of identification. By a “statistical victim,” I mean the person who, extrapolating from traffic records, will be in a similar, serious car accident tomorrow (and may then be identified), or the children who will fall into wells next year if we do not cap them better than we did the well that trapped Jessica. Does this disposition (or perceived obligation) have any normative force? I initially thought there could be no such normative force, but consequentialist and nonconsequentialist arguments, pro and con, have convinced me that reasonable people can disagree with each other. This disagreement poses a problem for political philosophy: how should policy choices take such disagreement into account?